The Effect of Saponite Clay on Ruminal Fermentation Parameters during In Vitro Studies - Alina Pikhtirova; Ewa Pecka-Kiełb; Bożena Króliczewska; Andrzej Zachwieja; Jarosław Króliczewski; Robert Kupczyński (Animals, 2024)
Reducing the emission of global warming gases currently remains one of the strategic tasks. Therefore, the objective of our work was to determine the effect of saponite clay on fermentation in the rumen of cows. The pH, total gas production, CH4, and volatile fatty acid (VFA) production in ruminal fluid was determined in vitro. Saponite clay from the Tashkiv deposit (Ukraine) has a high content of silicon, iron, aluminum, and magnesium. The addition of 0.15 and 0.25 g of saponite clay to the incubated mixture did not change the pH but reduced the total production (19% and 31%, respectively) and CH4 (24% and 46%, respectively) in the ruminal fluid compared to the control group and had no significant effect on the total VFA levels, but propionic acid increased by 15% and 21% and butyric acid decreased by 39% and 32%, respectively. We observed a decrease in the fermentation rates, with a simultaneous increase in the P:B ratio and an increase in the fermentation efficiency (FE) in the groups fermented with saponite clay, probably a consequence of the high efficiency in the breakdown of starch in the rumen. Therefore, further in vivo studies to determine the effective dose and effect of saponite clay on cow productivity and the reduction of gas emissions are promising and important.